2004
DOI: 10.1136/bjo/2003.020453
|View full text |Cite
|
Sign up to set email alerts
|

What patients want to know before they have cataract surgery

M J Elder

Abstract: Aims:To investigate what patients want to know before undergoing cataract surgery. Methods: A written questionnaire was answered by 190 patients prior to cataract surgery. Results: The five pieces of preoperative information rated most important were: chance of visual improvement; when vision would improve; overall risk of losing vision from the operation; effect of not having the operation, and the types of serious complications. When asked ''should you be warned of a serious complication if it has a risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
(8 reference statements)
4
11
0
Order By: Relevance
“…However, results of this study only partly agree on these findings. Results of the bivariate analysis show that patients were highly satisfied with both items reflecting information receiving, information about anesthesia, and undergoing operations, as observed in other studies [11,12,23]. However, the relation faded when performing the multivariate analysis, which might indicate that these aspects are not as relevant for patients than generally assumed.…”
Section: Medical and Service Aspects Associated With Overall Satisfacsupporting
confidence: 65%
See 1 more Smart Citation
“…However, results of this study only partly agree on these findings. Results of the bivariate analysis show that patients were highly satisfied with both items reflecting information receiving, information about anesthesia, and undergoing operations, as observed in other studies [11,12,23]. However, the relation faded when performing the multivariate analysis, which might indicate that these aspects are not as relevant for patients than generally assumed.…”
Section: Medical and Service Aspects Associated With Overall Satisfacsupporting
confidence: 65%
“…Studies have demonstrated that satisfaction is influenced by the amount of information given to patients [10], especially about benefits and risks of their surgery [11,12] as well as by the surgeon communication behaviors [13]. Lantz et al found in their analysis of data from patients receiving breast cancer surgical treatment that the match between patient preferences regarding decision involvement and their actual level of involvement is a strong indicator of satisfaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings here, earlier studies indicate that patients mostly value understanding the complication rate of surgical intervention20 and the likely extent of visual improvement 21. Ophthalmologists might address the former by noting the significant reduction in complication rates with modern phacoemulsification, and the latter through highlighting the excellent refractive results possible with modern biometric formulae and diagnostic instruments.…”
Section: Discussionsupporting
confidence: 77%
“…Patients want to be warned of rare complications, 93.5% would like to be informed if the risk is 1 in 50 and 62.4% if it is 1 in 1000. 21 However, the accuracy of recall of consent information is low, particularly, with respect to serious complications, which provides a challenge in preparation of the patients for what may be complicated surgery. 22 …”
Section: Introductionmentioning
confidence: 99%